The neuroprotective effects of Liuwei Dihuang medicine in the APP/PS1 mouse model are dependent on the PI3K/Akt signaling pathway - Yuan, Ye; Liu, Yamei; Hao, Li; Ma, Jinlian; Shao, Simai; Yu, Ziyang; Shi, Ming; Zhang, Zhenqiang; Zhang, Zijuan (Frontiers in Pharmacology, 2023)
Alzheimer’s disease (AD) is an age-related neurodegenerative disease that progressively impairs cognitive function and memory. The occurrence and development of Alzheimer’s disease involves many processes. In response to the complex pathogenesis of AD, the Traditional Chinese medicine formula Liuwei Dihuang Pill (LWD) has been shown to improve the cognitive function of AD animal models. However, the active ingredients and mechanism of action of LWD have not been fully elucidated. In this study, network pharmacological analysis predicted 40 candidate compounds in LWD, acting on 227 potential targets, of which 185 were associated with AD. Through network pharmacological analysis, the mechanism of action of LWD therapy AD is related to the inhibition of inflammatory response, regulation of neuronal state, and autophagy. In this experiment, LWD was detected in the APP/PS1 transgenic mouse model. The objective was to observe the effects of LWD on hippocampal learning and memory ability, Aβ clearance, autophagy and inflammatory response in APP/PS1 mice. The results showed that LWD improved long-term memory and working memory in APP/PS1 mice compared with the WT group. At the same time, LWD can increase the expression of hippocampal autophagy biomarkers, reduce the precipitation of Aβ, and the activation of microglia and astrocytes. Its mechanism may be related to the regulation of the PI3K/Akt signaling pathway. Thus, we demonstrate for the first time that LWD has a neuroprotective effect on APP/PS1 mice and provide theoretical foundation for the development of a new clinical treatment for AD.